Breaking Barriers: Indonesian EFL Pre-Service Teachers’ Challenges and Solutions in TEFL - Ramadhani, Putri Fadila; Fithriani , Rahmah (Jurnal Ilmiah Global Education, 2025)
This study explores the challenges faced by pre-service English teachers in Indonesia during their teaching practicum and the solutions they implemented to overcome these difficulties. Using a qualitative research approach with a narrative design, data were collected through observations, reflective teacher journals, and semi-structured interviews with ten pre-service teachers. The findings reveal three main challenges: pedagogical, motivational, and psychological barriers. Pedagogically, participants struggled to balance the complexity of the material with student engagement in heterogeneous classrooms. Motivational challenges included students’ perceptions of English as irrelevant to their daily lives, leading to low engagement. Psychological barriers, such as fear of making mistakes and language anxiety, significantly hindered students’ participation in speaking activities. To address these issues, pre-service teachers adopted strategies such as differentiated instruction, interactive teaching methods, and fostering a supportive classroom environment. These findings highlight the importance of comprehensive teacher training programs that equip pre-service teachers with practical teaching strategies and reflective practices. This study contributes to the growing body of research on teacher education and English language teaching by providing insights into effective pedagogical approaches to address classroom challenges in an EFL context.